Generalized spin precession equations - Stöckmann, Hans-Jürgen; Dubbers, Dirk (New journal of physics, 2014)
The Bloch equations, which describe spin precession and relaxation in external magnetic fields, can be generalized to include the evolution of polarization tensors of various ranks in arbitrary multipole fields. We show applications of the generalized spin precession equations using simple examples from atomic, nuclear and condensed matter physics, and compare the various approaches found in the literature. The derivation of the generalized Bloch equations can be considerably simplified using a particular bra-ket notation for irreducible tensors.
Gesehen am 29.07.2020